2022
DOI: 10.1111/desc.13232
|View full text |Cite
|
Sign up to set email alerts
|

Neural processing of moral content reflects moral identity in 10‐year‐old children

Abstract: Middle childhood seems to be crucial for the emergence of a moral identity, that is, an evaluative stance of how important it is for someone's sense of self to be moral.This study investigates the effects of moral identity on the neural processing of moral content in 10-year-old children. Participants were presented with scenes portraying prosocial and antisocial behavior, while electroencephalographic responses were collected. Analyses of event-related potentials (ERPs) showed that, for children with a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For children, it is more important to avoid mismatches between their moral identity goal and behavior (prevention) than to produce matches between this goal and behavior (promotion). In line with this view, Pletti and colleagues (2022) reported that for 10-year-old children with a strong moral identity observing antisocial behaviors captured more attentional resources than prosocial behaviors (as evidenced by event-related potentials). As the positivity bias eases in late childhood and adolescence and as real- and ideal-self become increasingly differentiated, this prevention-orientation makes room for a more promotion-oriented moral identity.…”
Section: Moral Identity Development and Virtue Acquisitionmentioning
confidence: 68%
“…For children, it is more important to avoid mismatches between their moral identity goal and behavior (prevention) than to produce matches between this goal and behavior (promotion). In line with this view, Pletti and colleagues (2022) reported that for 10-year-old children with a strong moral identity observing antisocial behaviors captured more attentional resources than prosocial behaviors (as evidenced by event-related potentials). As the positivity bias eases in late childhood and adolescence and as real- and ideal-self become increasingly differentiated, this prevention-orientation makes room for a more promotion-oriented moral identity.…”
Section: Moral Identity Development and Virtue Acquisitionmentioning
confidence: 68%
“…Krettenauer and Hertz (2015) therefore argued that research on moral identity development needs to expand into other developmental periods and broaden its conceptual and empirical base. In line with this suggestion, the moral identity of children has become a promising area of research (Engelmann & Rapp, 2018; Engelmann et al, 2012; Kingsford et al, 2018, 2022; Pletti et al, 2022; Tomasello, 2019). Research in this area suggests that moral identity emerges around the age of 6–7 years, thus much earlier than previously assumed (see also Krettenauer, 2022a).…”
Section: Trends In Moral Identity Development: Theoretical Frameworkmentioning
confidence: 98%
“…Traits are high-level construals, as they capture a person's behavior abstractly across time and places (Trope & Liberman, 2010). This is implicitly recognized when researchers who adapt the SIMIQ approach for studying children's moral identity add concrete descriptions to these abstract trait labels (e.g., Pletti et al, 2022).…”
Section: Modifications Of the Simiqmentioning
confidence: 99%
“…As prosocial behavior decreased over time, this group may therefore be prevention-oriented compared with promotionoriented (Krettenauer, 2022), in that they may be more motivated to avoid a negative reputation (i.e., why we see decreases in aggression) rather than build a positive reputation (i.e., why we see decreases in prosociality). Neuroscientific evidence supports this; children who identify as less moral may also need to use less cognitive processes to anticipate scenes of aggression (e.g., hitting) than more moral children (Pletti et al, 2022). By being able to anticipate aggressive actions better, these children may have the tools to anticipate and prevent aggressive actions.…”
Section: Profiles Of the Moral Self-conceptmentioning
confidence: 99%